Benchmarking Eco-Efficiency and Footprints of Dutch Agriculture in European Context and Implications for Policies for Climate and Environment - van Grinsven, Hans J. M.; van Eerdt, Martha M.; Westhoek, Henk; Kruitwagen, Sonja (Frontiers in Sustainable Food Systems, 2019)
The agricultural sector in the Netherlands is per unit of land the most productive and efficient sector in the European Union (EU). However, emissions of ammonia, surpluses of nitrogen and phosphorus, and use of pesticides per hectare of agricultural land are also among the highest in the EU. In spite of successful policies and farm measures to reduce this pollution, agriculture still constitutes the largest environmental pressure on biodiversity. Dutch agriculture, including horticulture, also contributes 14% (32 Mton CO2-eq in 2016) to the national emissions of greenhouse gasses (GHG). These emissions hardly decreased since 2000. In the current bid to meet the Paris Climate Agreement (PCA), the agricultural sector will need to reduce emission by 3.5 Mton in 2030. The relative reduction target for GHG by agriculture is 11% and less than the national target of 49%, but still is a challenge because the technical potential for reduction of methane and nitrous oxides is relatively small. Apart from technical measures and innovations, there is an increasing call in society for structural measures, like reduction of livestock, to assure an appropriate reduction of GHG emission from agriculture. However, there are also concerns about leakage effects when livestock production would increase elsewhere, e.g., in the EU, causing a net increase of GHG emission and increased local environmental pollution. We carried out a Life Cycle Analysis for production of milk, pork, poultry, potato, and wheat in other EU countries which disclosed that GHG emission per unit of product in the Netherlands is similar to that in Germany and France, while lower than in central and southern EU. Nitrogen and phosphorus surplus per unit of product for Dutch products often are higher due to the high use of manure. These results indicate that the risk of transboundary leakage effects likely is small when implementing PCA for agriculture in the Netherlands or stricter environmental policies, also when including reduction of livestock production. Further, growth of livestock production in other European regions might be avoided by climate policies or when consumption of livestock products would decrease due to increased consumer awareness or targeted interventions.